Heart murmurs and echocardiography findings in the normal newborn nursery. (24th July 2018) - Fenster, Michael E.; Hokanson, John S.
Abstract: Objective: To determine the clinical findings and management implications of echocardiograms performed on infants with murmurs in the nursery. Design: Retrospective cohort study conducted from January 2008 through December 2015. Patients in the study were followed by chart review for up to 5 years. In addition, a survey of nursery providers was conducted in February 2016. Setting: A single community hospital associated with a university. Patients: All 26 573 infants who received care in the normal newborn nursery were eligible for inclusion in the study. Infants with echocardiograms were analyzed. The survey was sent by e‐mail to all 135 physicians who work in the nursery. Outcome Measures: The primary outcomes include the specific findings on echocardiogram and whether the findings required an acute change in management, outpatient follow up, or were incidental findings. The primary survey question was how physicians would manage an otherwise asymptomatic newborn with a heart murmur. Results: Four hundred ninety‐nine infants had echocardiograms, and over the study period the utilization of echocardiography increased from 1.02% to 2.56% ( P  < .001) of all infants. Three hundred fifty‐four babies had echocardiography performed because of a heart murmur. One hundred sixty‐three (46.0%) of these echocardiograms were normal and 160 (45.2%) had findings that did not require additional care. Twenty‐three neonates (6.5%) had echocardiographic findings that necessitated outpatient follow‐up and 8 neonates (2.3%) required neonatal intensive care due to the findings on their echocardiogram. In total, 14 infants (4%) would go on to require heart surgery or interventional cardiac catheterization. 63/135 (47%) physicians completed the survey, with wide variations in the management of newborns with heart murmurs. Conclusions: The use of echocardiography in the normal newborn nursery has increased with time despite improved prenatal detection of heart disease and the use of pulse oximetry screening, and identifies significant heart disease in a small but important number of infants.